SS-31 Targets NOS2 to Enhance Osteogenic Differentiation in Aged BMSCs by Restoring Mitochondrial Function - Sen Duan; Qindong Zhang; Jinqiang Zhu; Jiaming Wang (Organogenesis, 2025)
This study delves into the rejuvenating effects of SS-31 on aged human Bone Marrow-Derived Mesenchymal Stem Cells (BM-MSCs), focusing on its potential to restore their diminished osteogenic differentiation capacity, a critical issue in geriatric medicine and bone tissue engineering. SS-31 significantly improved mitochondrial function, increasing ATP production by 35% and reducing ROS levels by 40% in aged BM-MSCs. Osteogenic differentiation was enhanced, as evidenced by a 2.8-fold increase in ALP activity and a 3.5-fold increase in Alizarin Red S staining intensity. Additionally, SS-31 reduced NOS2 expression by 50%, highlighting its therapeutic potential in age-related bone loss. SS-31 intervention not only normalizes mitochondrial structure and function, reducing ROS levels and enhancing oxygen consumption rates, but also targets the NOS2 gene, a potential drug target, which upon knockdown, leads to a substantial upregulation of osteogenic markers and an improvement in mitochondrial function. In conclusion, the findings of this study highlight the therapeutic potential of SS-31 in reversing the age-related decline in BM-MSC function by specifically inhibiting NOS2 expression and restoring mitochondrial function. This research provides a scientific basis for the development of new treatments for osteoporosis and other age-related bone diseases, emphasizing the importance of targeting mitochondrial function and cellular senescence in regenerative therapies.